Cost-effectiveness of Tisagenlecleucel vs Standard Care in High-risk Relapsed Pediatric Acute Lymphoblastic Leukemia in Canada - Furzer, Jill (JAMA Oncol, 2020)
IMPORTANCE: Tisagenlecleucel, a chimeric antigen receptor T-cell therapy for relapsed or refractory pediatric acute lymphoblastic leukemia, has been approved for use in multiple jurisdictions. The public list price is US $475 000, or more than CaD $600 000. Assessing the cost-effectiveness of tisagenlecleucel is necessary to inform policy makers on the economic value of this treatment. OBJECTIVE: To assess the value for money of tisagenlecleucel compared with current standard care for tisagenlecleucel-eligible pediatric patients with acute lymphoblastic leukemia under unknown long-term effectiveness. DESIGN, SETTING, AND PARTICIPANTS: A cost-utility analysis of tisagenlecleucel compared with current standard care using a Canadian population-based registry of pediatric patients with acute lymphoblastic leukemia was performed. Results from 3 pooled single-arm tisagenlecleucel clinical trials and a provincial pediatric cancer registry were combined to create treatment and control arms, respectively. The population-based control arm consisted of patients meeting clinical trial inclusion and exclusion criteria, starting at second relapse. Multistate and individual-level simulation modeling were combined to predict patient lifetime health trajectories by treatment strategy. Tisagenlecleucel efficacy was modeled across long-term cure rates, from 10% to 40%, to account for limited information on its long-term effectiveness. Uncertainty was tested with 1-way and probabilistic sensitivity analysis. Data were collected in September 2017, and analysis began in December 2017. EXPOSURES: Tisagenlecleucel compared with current standard care for tisagenlecleucel-eligible patients. MAIN OUTCOMES AND MEASURES: Relative health care costs, survival gains, and quality-adjusted life-years (QALYs) between tisagenlecleucel and current standard care. RESULTS: The treatment and control arms were modeled on 192 and 118 patients, respectively. The mean (SD) age of control individuals was 10 (4.25) years, and the mean (SD) age of the pooled clinical trial sample was 11 (6) years. The control individuals had 78 boys (66%), and the pooled clinical trial sample had 102 boys (53%). Treatment with tisagenlecleucel was associated with an additional 2.14 to 9.85 life years or 1.68 to 6.61 QALYs, compared with current care. The average additional cost of tisagenlecleucel was CaD $470 013 (US $357 031). Accounting for the total discounted cost over the patient lifetime resulted in an incremental cost of CaD $71 000 (US $53 933) to CaD $281 000 (US $213 453) per QALY gain. CONCLUSIONS AND RELEVANCE: To our knowledge, this study offers the first cost-effectiveness analysis of tisagenlecleucel compared with current standard care for pediatric patients with acute lymphoblastic leukemia using a constructed population-based control arm. At a willingness-to-pay threshold of $150 000/QALY, tisagenlecleucel had a 32% likelihood of being cost-effective. Tisagenlecleucel cost-effectiveness would fall below $50 000/QALY with a long-term cure rate of over 0.40 or a price discount of 49% at its currently known effectiveness.